Analisa Penyimpangan Sinyal GPS Pada Share Location di Urban Area - Made Sutha Yadnya; Putri Zahrina; I Wayan Sudarta (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
This research arose because there was an error or shift from the share location on the smartphone. As for evaluating the accuracy of share location with several variations of smartphones that are usually used by goods delivery services using WhatsApp and Telegram applications using four android smartphones by comparing RMSE and CDF values. The results show that the average RMSE WhatsApp error is 11-21 meters, while Telegram is 16-37 meters. WhatsApp's CDF on S4 shows the lowest error distribution around a low of less than 20 meters, while Telegram's PDF shows an error distribution of around 30 meters. In the CDF analysis, WhatsApp showed a faster distribution reaching a value of 1, indicating higher accuracy, while Telegram had a slower and wider distribution, indicating lower instability and accuracy.